The Effect of Think Pair Share and Intelligence Quotient on Economics Students’ Learning Outcome - Naskah Naskah; Ansharullah Ansharullah; Harum Natasha; Hendra Riofita (STAI Hubbulwathan Duri, 2022)
The purpose of this study was to examine the relationship between intellectual ability, the Cooperative type think pair share learning model, and the Entrepreneur lesson in grade ten at a vocational high school in Sungai Penuh. This study is a Quasi-experiment in nature. Purposeful sampling was used in this study. In total, 103 students made up the study's sample. We used two instruments to obtain this data: an experimental one and a validated one. The school has collected primary data in the form of student learning outcomes and secondary data in IQ test outcomes. On the other hand, a descriptive and inductive analysis was performed using a two-way analysis of variance. The study found that (1) the learning outcomes for students who were taught using the cooperative learning model type Think Pair Share were better than the outcomes for students who were taught using the traditional learning model. According to his research, the academic success of high-IQ students is not better than that of low-IQ students. Thirdly, there was no correlation between the cooperative learning approach (Think, Pair, Share) and student achievement.